Preparedness and Response for a Nuclear or Radiological Emergency Involving the Transport of Radioactive Material - IAEA (IAEA, 2022)
Provides guidance and recommendations on arrangements to be made at the preparedness stage, as part of overall emergency preparedness, for emergencies involving the transport of radioactive material. The guidance and recommendations are aimed at any State and its government, and at regulatory bodies and other response organisations.
Description based upon print version of record.
Keywords: Radiology.; elektronické knihy; electronic books